Inhibition of Edible Plant Torch Ginger (Etlingera elatior (Jack) R. M. Sm.) against Î±-Glucosidase and Î±-Amylase - Syafni, Nova; Fakhriadi, Athallah; Nofrizal, Nofrizal; Ismed, Friardi; Putra, Deddi Prima (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
Indonesia's diabetes cases were in the top ten list globally, with 90% of the patients being type-2 diabetes mellitus (T2DM).Â  An approach for screening the local edible plants is made for managing or treating T2DM by inhibiting Î±-glucosidase and Î±-amylase enzymes. Results showed that inflorescence of Etlingera elatior inhibition toward both enzymes. TLC-autography and IC50 value of fractions from E. elatior were used to identify the potential fractions and possible compounds for the activity. The non-polar fraction was spotted in the active substances based on TLC-autography. Then, the targeted compounds were separated by column chromatography to obtain stigmasterol as one of the active compounds. The IC50 values of total extract, n-hexane, EtOAc, BuOH, and isolated compound against Î±-glucosidase were 16.0, 7.5, 13.5, 9.7, and 2.0 ppm, respectively. The IC50 values for Î±-amylase inhibition were respectively 88.6, 48.6, 23.2, 29.1, and 27.5 ppm. The positive control (acarbose) against Î±-glucosidase and amylase exhibited IC50 values of 153.2 and 12.3 ppm. The inhibition of E. elatior against the two enzymes could be an alternative to delay carbohydrate absorption.